2003
DOI: 10.1515/znb-2003-0109
|View full text |Cite
|
Sign up to set email alerts
|

Peri-Interactions in Naphthalenes, 9 [1]. On Hypercoordination in Non-Quaternary Phosphonium Salts and a Secondary Phosphine with the (8-Dimethylamino-Naphth-1-Yl) Substituent

Abstract: The 31P NMR data of non-quaternary (8-dimethylamino-naphth-1-yl)phosphonium salts, with emphasis on the 1J(31P, 1H) coupling constants, where scrutinized for their potential to yield information about N→P dative interactions. As for δ (29Si) and 1J(29Si, 1H) in the isosteric silanes, the data do not permit conclusions in favour of such interactions. 1J(31P, 1H) of bis(8-dimethylaminonaphth- 1-yl)phosphine in conjunction with the distances d(N···P) invalidates the basic assumption on which the claim of dative N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Sceptical of the claims made by Corriu, Chuit and others, they reinvestigated the structure and properties of DAN-phosphines and related compounds. [53,[62][63][64][65][66] Several structural and spectroscopic properties of the DAN-phosphorus compounds led them to conclude that an intramolecular dative bond was highly unlikely and no hypercoordination would be anticipated. Firstly, they believe N···P distances shorter than sum of van der Waals radii of the respective elements are not an indication of a bonding interaction, instead they are enforced by the geometry of the rigid naphthalene backbone.…”
Section: Mixed Nappx Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sceptical of the claims made by Corriu, Chuit and others, they reinvestigated the structure and properties of DAN-phosphines and related compounds. [53,[62][63][64][65][66] Several structural and spectroscopic properties of the DAN-phosphorus compounds led them to conclude that an intramolecular dative bond was highly unlikely and no hypercoordination would be anticipated. Firstly, they believe N···P distances shorter than sum of van der Waals radii of the respective elements are not an indication of a bonding interaction, instead they are enforced by the geometry of the rigid naphthalene backbone.…”
Section: Mixed Nappx Systemsmentioning
confidence: 99%
“…Other arguments, such as high-field shift of the phosphorus NMR signal on intramolecular DAN coordination (or its absence) were questioned by Schiemenz; additional support for non-existence of the dative bond was found in analysing the J(CH) coupling constants of NMe 2 groups [64] or the study of NMR properties of protonated DAN-phosphines. [62] During these comparative studies a range of DAN-phosphines and related compounds were synthesized by Schiemenz (Scheme 38) [62,63,[67][68][69] and (Scheme 34). [55] Schiemenz concluded that under favourable conditions DAN-phosphorus compounds can form dative N!P bonds and hexacoordination at phosphorus can occur, an example of this is molecule 64 (Scheme 34).…”
Section: Mixed Nappx Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the perfect naphthalene system, the available intersubstituent distance is only 247 pm [4, 5, 39 -42] so that even strong distortion of the C 10 system does not permit Σr(vdW) distances [1, 11,42]. To accommodate bulky peri-substituents, the C 10 system resorts to an enlargement of the bay angles substituent-C(1/8)-C(9) and C(1)-C(9)-C(8) (predominantly of the latter one [4,5,11,12,43]) whereas the C 10 skeleton frequently remains virtually planar [12,18,42,44,45]. In 1a, the planarity is borne out by the sum of the angles around C(1), C(8) and C(9), consistently 360 • .…”
Section: Di(8-phenylthio-naphth-1-yl) Disulfide (1a)mentioning
confidence: 99%